Dental care for cerebral palsy patients using auxiliary resources to inhibit pathological tonic reflexes - Aguiar, Sandra Maria Herondina Coelho Ávila; Alves-Rezende, Maria Cristina Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Cerebral paralysis is a chronic illness that affects the central nervous system. In this article the author describes the techniques used at CAOE (Odontological Center for Assistance to patients with special needs) to restraint CP patients during dental treatment, because they present some pathological reflexes which interfere in their odontological assistance. Also it shows how to perform a special physical restraint and how to keep the mouth open by using simple tools including a homemade one. All the devices used during the dental treatment in cerebral palsy patients, such as the physical restraint with bands or sheet to wrap them up, cylindrical pad or cushion made of a soft material, or simple tools including a homemade one to keep the mouth open are usually and safely used in CAOE. All these simple devices are necessary, because there are no available funds for the acquisition of expensive material or equipment. Despite of a shortage of resources we can easily and efficiently assist these patients. Keywords: Cerebral Palsy; Patient Care; Restraint, Physical; Reflex